Cytotoxic effect of filtering respiratory protective devices from the waste sorting industry: is in vitro toxicology useful for risk characterization? - Viegas, Carla (2020)
The use of Filtering Respiratory Protective Devices (FRPD) is mandatory in Portugal to protect workers from the waste industry of harmful exposures. Deleterious health effects of exposure to bioburden via inhalation and/or ingestion include respiratory symptoms and nephrotoxicity. Between January and February 2019, 118 FRPD samples were collected in one waste sorting industry and characterized regarding microbial contamination and cytotoxicity, defined as cell metabolic activity, through the MTT colorimetric assay (3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide). Cytotoxic effect was classified according to the percentage of extinction values with respect to the control group, as follows: absent (≥90); low (80% to 90%, +); medium (60% to 79%, ++); and high (below 60%, +++). For 113 samples the MTT assay revealed a cytotoxic effect in A549 cells, of which 81 presented high cytotoxicity. In SK cells, a cytotoxic effect was observed in 56 samples, of which five displayed a high cytotoxic effect. Several moderate (p<0.05) to strong (p<0.01) correlations were found between higher bacterial and fungal counts both in interior layers (fungi and bacteria) and in exhalation valves (fungi) of FRPD samples and reduced cellular metabolic activity of SK cells. On the basis of the obtained results for the cytotoxic effect of FRPD samples on two different cells lines, it was determined that A549 cells exhibited a cytotoxic effect for a higher number of FRPD, whereas the SK cells model correlated better with the other assessed parameters, namely, bacterial and fungal load and conditions of FRPD use. Although the results are not conclusive on the most appropriate cell line to assess FRPD cytotoxicity, they reinforce the importance of in vitro toxicology in exposure assessments to determine the cytotoxicity of mixtures of contaminants, for better risk characterization and selection of appropriate risk management measures.